Feasibility of training community health workers to conduct periodontal examinations: a validation study in rural Nepal - Daniel J. Erchick; Nitin K. Agrawal; Subarna K. Khatry; Joanne Katz; Steven C. LeClerq; Bhola Rai; Mark A. Reynolds; Luke C. Mullany (BMC, 2020)
Abstract Background In many low- and middle-income countries, insufficient human resources limit access to oral health services. Shifting clinical tasks to less specialized health professionals, such as community health workers, has been used as a strategy to expand the health workforce, especially in remote or underserved locations. The objective of this study was to evaluate the validity of periodontal examinations conducted by auxiliary nurse midwives in a rural home setting in Nepal. Methods Twenty-one pregnant women < 26 weeks gestation from Sarlahi District, Nepal, underwent full mouth periodontal examinations measuring probing depth (PD) and bleeding on probing (BOP) on 6 sites per tooth by one of five auxiliary nurse midwives, who were trained for this study but had no previous training in dentistry. After a 15-min break, each participant was examined again by an experienced dentist. Measures of validity for PD and BOP were calculated comparing the pooled and individual auxiliary nurse midwives to the dentist. A multivariable GEE model estimated the effect of periodontal characteristics on agreement between the auxiliary nurse midwives and the dentist. Results Participant mean age was 22 years (SD: ±3 years), mean PD was 1.4 mm (SD: 03 mm), and 86% of women had BOP (according to the dentist). Percent agreement, weighted kappa scores, and intraclass correlation coefficients for PD, with an allowance of ±1 mm, exceeded 99%, 0.7, and 0.9, respectively, indicating an acceptable level of agreement. Auxiliary nurse midwives tended to report higher PD scores relative to the dentist, although this over-estimation was small and unlikely to impact population-based estimates of important indicators of oral health status. GEE regression modeling indicated similar agreement for mandible vs. maxilla, left vs. right side, and PD (≤2 mm, > 2 mm), and lower agreement for posterior teeth and lingual and proximal sites. Conclusion Auxiliary nurse midwives were able to accurately conduct periodontal examinations in a rural home setting, suggesting the potential to shift tasks away from highly trained dentists and periodontal examiners in low-resource communities. Trial registration ClinicalTrials.gov Identifier: NCT01177111 (Nepal Oil Massage Study); registered on August 6th, 2010.